Implementation and Optimization of Digital Ticket Applications Using Java in Online Sales Systems - Khairunnisa Samosir; Nurkhasanah Rina Puspita (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
Online digital ticket sales have become one of the main methods of distributing tickets for various events, from concerts to transportation. Although many digital ticketing applications are available, there are significant challenges regarding performance, security, and integration with payment systems. This research aims to implement and optimize a digital ticket application using Java in an online sales system to increase efficiency and security. This research methodology includes the development of Java-based applications with a microservices architecture approach, which allows separation of functionality and increases scalability. This application is designed to manage the ticket purchasing process, including event selection, payment, and electronic ticket delivery using QR Code technology for verification. In the implementation process, Spring Boot technology was used for server-side development and JavaFX for the user interface. The results of this research show that the Java-based digital ticket application developed can manage transactions efficiently and safely, and can handle high user volumes without significant performance degradation. These findings provide an important contribution in the field of digital ticket application development and can be used as a reference for implementing similar systems in various sectors.